Validation of the Interpersonal Reactivity Index (IRI) in a Uruguayan sample - Martin Bidegain; Marcela Carballo; Daniel Costa-Ball (Ciencias Psicológicas)
Background: The Interpersonal Reactivity Index (IRI), introduced by Davis in 1980, remains a widely used self-report tool designed to assess empathy from a multidimensional perspective, with adaptations for various languages and populations. However, many studies examining its psychometric properties have failed to replicate the original four-factor structure. Method: This instrumental study applied Classical Test Theory to adapt the IRI for use in Uruguay, with a sample of 858 adult participants (640 females, 218 males). Results: The original 28-item scale did not show a good fit with the four-factor model. Removing the reversed items led to an acceptable fit for both the original and a three-factor model. Conclusion: These findings suggest that a shortened version of the scale, excluding the reversed items, would be more suitable for this population. Further research on the impact of reversed items is recommended. The study highlights the importance of ongoing investigation into the psychometric properties of the IRI, as well as the theoretical and practical implications of using a shortened version.